Size limits for rounding of volcanic ash particles heated by lightning. Issue 3 (30th March 2017) - Wadsworth, Fabian B.; Vasseur, Jérémie; Llewellin, Edward W.; Genareau, Kimberly; Cimarelli, Corrado; Dingwell, Donald B.
Abstract: Volcanic ash particles can be remelted by the high temperatures induced in volcanic lightning discharges. The molten particles can round under surface tension then quench to produce glass spheres. Melting and rounding timescales for volcanic materials are strongly dependent on heating duration and peak temperature and are shorter for small particles than for large particles. Therefore, the size distribution of glass spheres recovered from ash deposits potentially record the short duration, high‐temperature conditions of volcanic lightning discharges, which are hard to measure directly. We use a 1‐D numerical solution to the heat equation to determine the timescales of heating and cooling of volcanic particles during and after rapid heating and compare these with the capillary timescale for rounding an angular particle. We define dimensionless parameters—capillary, Fourier, Stark, Biot, and Peclet numbers—to characterize the competition between heat transfer within the particle, heat transfer at the particle rim, and capillary motion, for particles of different sizes. We apply this framework to the lightning case and constrain a maximum size for ash particles susceptible to surface tension‐driven rounding, as a function of lightning temperature and duration, and ash properties. The size limit agrees well with maximum sizes of glass spheres found in volcanic ash that has been subjected to lightning or experimental discharges, demonstrating that the approach that we develop can be used to obtain a first‐order estimate of lightning conditions in volcanic plumes. Key Points: New dimensional analysis to scale heating, melting, rounding, and cooling of particles Quantitative upper bound on the particle size for thermal equilibrium, melting, and rounding Conceptual framework for surface tension‐driven dynamics of molten volcanic droplets